Systematic literature review of international assignment impact on expatriates’ career competencies - Zeng, Cheng (Cranfield University, 2005)
Expatriate career management upon returning home is both a challenge to the individual and the employing multinationals, however, most studies took only organisational view to explain the challenge. How international assignment impacts on expatriates’ career competencies is not clear. This study employs the systematic literature review approach to survey on the present knowledge of international assignment impact on expatriates’ career competencies. The systematic review aims to systematically identify studies, critically review their diverse range of propositions and empirical evidences, and then explicitly extract evidence about the career competency impacts of international assignments for synthetic analyses. I detail the systematic review protocol for the research question and reflect on the implementation of literature search and selection procedures. Following its procedures, I selected 45 key papers for comprehensive data synthesis. Sufficient evidence of international assignment impact on all three dimensions of expatriates’ career competencies is found. Through the review of theoretical propositions and empirical evidence, five specific thematic groups of career competency are found and emerge from the ‘know-why’ dimension of career competencies, while four thematic groups emerge for each of the ‘know-how’ and ‘know-whom’ dimensions. The number of studies about of international assignments’ impacts on expatriates’ ‘know-how’ and ‘know-why’ dimensions are much more than the ‘know-whom’ dimension, which suggests the lack of exploration about the latter despite its significant effects on expatriate performance and career adjustment issues identified in the past. I also found expatriate’s career competencies of value systems, language skills and career strategy, and private non-work relationships are much less studied and yet important career competencies in intercultural contexts. They are thus candidates of my future research. Finally, I examine the limitations of the systematic review approach in this study. I conclude some learning experiences on the systematic review, which contribute to future researcher with the approach.